Encouraging Circular Waste Economies for the New Zealand Construction Industry: Opportunities and Barriers - Low, Joanne K.; Wallis, Shannon Lee; Hernandez, German; Cerqueira, I. S.; Steinhorn, G.; Berry, Terri-Ann (Frontiers in Sustainable Cities, 2020)
As our global population increases, the resulting waste mountain continues to rise. It has been identified that the Construction Industry contributes to a large proportion of the waste to landfill (and cleanfill) sites. Whilst there have been a multitude of commercial ventures and research-based activities targeted to challenge waste volumes, the ambitions of a truly circular economy for this industry remain far from realised. This article will discuss industry examples of waste minimisation initiatives which have been implemented successfully to support a less linear approach and encourage sustainable waste management for industrialised nations. We also identify limitations of this decentralised approach to resource management and suggest how the creation of resource markets, on both national and international scales, could connect the waste management loop for a vastly improved environmental outcome.